One-day bowel preparation in children with colostomy using normal saline - Emmanuel A Ameh; Christopher S Lukong; Philip M Mshelbwala; Mark A Anumah; Alexander Gomna (Wolters Kluwer Medknow Publications, 2011)
Background: Colonic and colorectal surgery frequently requires bowel preparation. This is an evaluation of the use of normal saline for one-day bowel preparation in children with colostomy. Patients and Methods:A prospective study of 55 children with colostomy who had one-day bowel preparation for colonic and colorectal surgical procedures in a 3-year period. The information, along with clinical data was recorded on a structured proforma. Data were analysed using SPSS version 11.0. Results:There were 33 boys and 22 girls. The median age was 4 years (range, one month - 13 years). The primary diagnosis were as follows: Anorectal malformation, 24 (44%); Hirschsprung`s disease, 24 (44%); Faecal incontinence- post-abdominoperineal pull-through, 2 (4%); Penetrating rectal injury, 1 (2%); others, 4(8%). Intraoperative bowel luminal fluid cleanliness was assessed as clear in 36 (62%) and contaminated in 21 (38%). Overall, postoperatively, superficial surgical site infection occurred in 6 (10.9%) patients (2 had clean intraoperative colonic fluid, 5.9%. Conclusion:One-day bowel preparation using normal saline is effective and safe in children with colostomy.